HUBUNGAN DISMENOREA PRIMER DENGAN KEBIASAAN OLAHRAGA PADA MAHASIWI FAKULTAS KEDOKTERAN UNIVERSITAS BAITURRAHMAH ANGKATAN 2021 - Habil Erlangga; Berri Rahmadhoni (Nusantara Hasana Journal, 2025)
Primary dysmenorrhea is a complaint of menstrual pain that often occurs in women of productive age, especially among female students, which can disrupt daily activities. One of the non-pharmacological methods that can be used to reduce dysmenorrhea symptoms is regular exercise. Less active exercise habits are one of the risk factors, while regular exercise has been proven effective in reducing pain through increased endorphins and blood flow. Objective: This study aims to analyze the relationship between exercise habits and the severity of primary dysmenorrhea among the 2021 cohort of female students at the Faculty of Medicine, Baiturrahmah University. Method: This study used an observational analytic design with a cross-sectional approach on 68 respondents selected through consecutive sampling. Data were collected using the Numeric Rating Scale (NRS) pain intensity questionnaire and the Godin-Shepard Leisure-Time Physical Activity Questionnaire. Results: The research findings indicate that the majority of respondents have less active exercise habits (69.1%), with 45.6% of respondents experiencing severe dysmenorrhea pain. Bivariate analysis shows a significant relationship between exercise habits and the intensity of primary dysmenorrhea (p-value = 0.000). Female students who regularly engage in exercise have a lower level of pain compared to those who are less active. Conclusion: This study concludes that exercise habits play an important role in reducing primary dysmenorrhea symptoms. Therefore, it is important for female students to maintain a regular exercise routine to improve their quality of life. This research also recommends the development of structured exercise programs to reduce the risk of primary dysmenorrhea.